Pulsatile Proptosis due to Intraorbital Meningocele - van Rumund, Anouke; Verrips, Aad; Verhagen, Wim I. M. (Frontiers in Neurology, 2017)
We present a case of a 79-year old man with a non-symptomatic pulsatile proptosis of the left eye. Magnetic resonance imaging revealed a meningocele into the left orbit due to an osseous defect in the orbital roof.